Rethinking federalism - Law, J (2010)
This thesis is motivated by uncertainty in the academic literature surrounding the meaning of federalism and the appropriate usage of the concept to describe political systems. In particular, its use in characterising systems of regional integration which have moved beyond a strictly inter-governmental character, but not yet reached Statehood, is today highly contested, as in the case of the European Union. The established consensus that this entity constitutes a wholly novel ‘sui generis’ form, neither federal nor confederal in character, has been tempered in recent years by a growing willingness among scholars to deploy the lens of comparative federalism to analyse the polity. However, the precise relevance of the concept in this new context remains unsettled. Can political science achieve any more definite understanding that removes such doubt? I consider this question through the perspective of the history of ideas, by examining the evolution of federalism from inception to the present day. I argue that the history of the federal idea in the United States reveals that the heart of the problem lies in confusion over the nature of sovereignty. Ever since Philadelphia federalism has been thought to mean ‘a division of sovereignty’. However, the subsequent Civil War did appear to demonstrate that the notion of sovereignty shared between two levels of government was a false construction: either the whole or the parts could be sovereign, but not both simultaneously. This point, it seems - the indivisibility of sovereignty - was not fully taken on board afterwards in the United States and elsewhere. The thesis seeks to put this right and to systematically relate the evolving concept of federalism with the evolving and contested nature of sovereignty. On this ground, I suggest that we clarify the definition of federalism as ‘a division of the powers flowing from sovereignty’. This in turn yields two specific varieties of ‘compound polity’ where before only one was known: the single State and multi-State federal forms. The latter has to date been an unobserved species, which, it would seem, the fact of the EU’s existence now forces us to recognize.